Szkoła jako jeden z elementów systemu oświaty. Zagadnienia prawne - Pyter, Magdalena (Przegląd Prawno-Ekonomiczny, 2007)
Streszczenie dostępne wyłącznie w języku angielskim: The system of polish education is object of this article . It is concered in Poland in foothold act about system of education from 7 September 1991. System of education include educational institution, education is purpose which, fostering and prosecution of protection over children and young people. Author of this article particularly has taken into consideration that ”school” is one of element in this system . School is basic, important and in article of system of education fundamental element . According to polish law school can be public and unpublic. Founders and public schools can be organs leading units of local govemments, legal entities and physical persons. Public schools can also set up and lead individual ministers. Founder and physical persons can lead exclusively and legal unpublic school.